Galectin-related protein: an integral member of the network of chicken galectins 1. From strong sequence conservation of the gene confined to vertebrates to biochemical characteristics of the chicken protein and its crystal structure - García Caballero, Gabriel; Flores-Ibarra, Andrea; Michalak, Malwina; Khasbiullina, Nailya; Bovin, Nicolai V.; André, Sabine; Manning, Joachim C.; Vértesy, Sabine; Ruiz, Federico M.; Kaltner, Herbert; Kopitz, Jürgen; Romero, Antonio; et al. (Biochimica et biophysica acta. General subjects, 2016)
Background - Endogenous lectins are multifunctional effectors in cell physiology. Adding the sixth member of the galectin family in chicken, a model organism for systematic profiling of these adhesion/growth-regulatory proteins, is a step toward comprehensive network monitoring. - Methods - Database mining and computational data processing are applied for gene detection, chromosomal location and sequence alignments. Cloning, recombinant production and fusion-protein technology gain access to the protein, mass spectrometry and gel electrophoresis/filtration provide analytical data. Haemagglutination, glycan microarray and cell assays assess binding capacity, and crystallography of a shortened variant (also analyzed by ultracentrifugation and small angle X-ray scattering) determines its structure. - Results - The gene for the galectin-related protein (GRP) is present exclusively in vertebrates with high-level sequence conservation and similar chromosomal positioning. The chicken protein is monomeric and has lost the canonical galectin property of binding lactose. The crystal structure of the variant without the 36-amino-acid extension at the start provides explanations for this lack of binding. - Conclusions - Chicken GRP is special within this family of six proteins by being unable to bind lactose. The documented high degree of sequence conservation among vertebrate orthologues confers the status of a model for delineating an assumedly shared functionality to this GRP. - General significance - Biochemical characterization of a product of a gene under strong positive selection is a prerequisite for functional characterization. It is also essential for network monitoring by adding a new member to this lectin family.
Gesehen am 28.04.2020